Design and Standardization a Test to Measure Speed Accuracy and Skill Level of Floor Defense for Libero in Volleyball - Jumaa Ismail Jumaa (Program Studi Pendidikan Kepelatihan Olahraga, 2026)
The current study aims to designing a test to measure speed, accuracy, and skill performance level of libero's floor defense skill, Setting standard scores to test speed, accuracy, and skill level of libero's floor defense skill. The researcher used descriptive survey method as it was suitable for nature of study. Study community was defined as a number of volleyball players representing clubs in northern region participating in Elite League and Premier League for 2025/2026 Sports season, totaling 185 players distributed across 15 clubs. Sample was selected from study community purposively, consisting of 30 players Liberos, representing 16.85%. Results showed that reaching a test to measure speed and accuracy of skillful court defense performance of libero in volleyball Based on high scientific principles, to arrive at tables specific to grades and standard levels of test designed to measure speed and accuracy of skill performance of floor defense skill for Libero in volleyball. The researcher recommends that adopting the test that was designed and standardized to be a standard tool for measuring speed and accuracy of skill performance of floor defense skill for Libero in volleyball, in order to ensure objectivity and accuracy of results, Adopting standard grades and levels in evaluating level of players, with possibility of using these levels as a reference to determine strengths and weaknesses of Libero in skill of floor defending.